A Report on the Bioecology of the Giant Red Bug, Macroceroea (Loidta) Grandis (Gray) (Family: Pyrrhocoridae) and its Conservation in the Bidbhutmhusan Wild Life Sanctuary, Parmadan, West Bengal - Mitra, Bulganin; Banerjee, Dhriti; Mridha, R. S. (Indian Forester, 2011)
The present study reveals that the integral association of the ’giant red bug’ Macroceroea (Lohita) grandis (Gray) with the false white teak tree, with regards to its saprozoic feeding and all other essential biological activities need the presence of the host plant species and its loss is directly related with the existence of the bug. Though insects are overlooked when forest management issues are discussed, proper management of our forests however should not exclude the forest associated and dependant fauna. Even innocuous actions like clearing of forest, removal of leaf litter and rotting fruits (as in the present case) can actually have larger implicatious like habitat loss for a species. Thus, while planning forest management and conservation strategy even these smaller issues should be kept in mind.